Search of the flow curve for low density polyethylene for the rectangular channel - Сівецький, Володимир Іванович; Рябінін, Дмитро Дмитрович; Сокольський, Олександр Леонідович; Кривко, Сергій Антонович; Франкова, Маргарита Вікторівна (Eastern-European Journal of Enterprise Technologies, 2012)
In article the method of the curves current polymers reduction , not invariant concerning hydraulic radius of the channel, to an invariant kind, in particular, for use possibility the viscosimetry data is offered at calculations of not round channels